Coastal morphodynamical modelling in nonlinear shallow water framework using a coordinate transformation method - Huynh, Van Long; Dodd, Nicholas; Zhu, Fangfang (Elsevier, 2017)
A 1D numerical model of Nonlinear Shallow Water Equations (NSWEs) coupled to an advection equation for suspended sediment and a bed evolution equation is developed. The moving boundary at the shoreline is treated by a coordinate transformation method (CTM). An absorbing-generating seaward boundary condition in the transformed variables is also developed. The purely hydrodynamic component (NSWEs) is verifed against analytical results. The NSWEs plus advection equation is verifed quasi-analytical results. The fully-coupled model with bed change due to bed-load is verifed against a single swash event and long-term numerical simulation. Excellent agreement is observed in all verifcations.